Collaborative versus non-collaborative knowledge transfer mechanisms in externally stimulated innovations - Galvin, Peter (Curtin University of Technology, 2006)
Externally stimulated innovations require some form of knowledge transfer to move appropriate knowledge into the innovating organization. These knowledge transfer mechanisms may take a variety of forms, though within the academic literature there is an implied emphasis upon different forms of collaborative relationships. This focus is demonstrated through a review of six prominent journals in the field. This paper seeks to test whether this emphasis upon collaboration is justified. In doing so, a basic knowledge transfer classificatory system was developed to classify how knowledge was transferred for 61 externally stimulated innovations in the bicycle industry. The results indicated that knowledge transfer mechanisms that involved no direct collaboration were used far more frequently than the different collaborative style mechanisms. This result contrasts significantly to the existing literature, possibly suggesting that the focus upon collaborative relationships in the innovation process in somewhat misplaced.